2006
DOI: 10.1113/jphysiol.2006.116657
|View full text |Cite
|
Sign up to set email alerts
|

Organization and function of ICC in the urinary tract

Abstract: ICC are found in both the upper and lower urinary tract. They are not found in the ureter itself but are confined to the lamina propria of the renal pelvis and pelvi-calyceal junction. They do not appear to have a primary pacemaker role (this is ascribed to atypical smooth muscle cells in the same location) but rather conduct and amplify the pacemaker signals generated by the atypical smooth muscle cells. In the bladder, ICC are widely distributed in the sub-urothelial region, in the lamina propria and at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
40
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 31 publications
5
40
0
1
Order By: Relevance
“…On the other hand, during voiding, the urethra relaxes and the detrusor contracts to facilitate emptying of the bladder (36). An isolated rat urethral preparation is "continent" in the absence of external neural input, but flow ensues when the smooth muscle is relaxed (29). Furthermore, stimulation of the skeletal muscle makes remarkably little difference to the ability of the contracted urethra to retain fluid.…”
mentioning
confidence: 99%
“…On the other hand, during voiding, the urethra relaxes and the detrusor contracts to facilitate emptying of the bladder (36). An isolated rat urethral preparation is "continent" in the absence of external neural input, but flow ensues when the smooth muscle is relaxed (29). Furthermore, stimulation of the skeletal muscle makes remarkably little difference to the ability of the contracted urethra to retain fluid.…”
mentioning
confidence: 99%
“…The existence of CLC in the upper and lower urinary tract has been clearly shown before (Hashitani 2006, McHale et al 2006, Lang et al 2007). The present study revealed numerous IC that did not form a clear network.…”
Section: Discussionmentioning
confidence: 83%
“…Мочевой пузырь большую часть времени функционального цикла ведет себя как орган кумуляции мочи, при этом в различных областях мышечного слоя наблюдается аналогичный электрический базовый ритм. В этом же временном интервале уретра контрактирует препятствуя утечке мочи и создавая тем самым условия для продолжительного мышечного тонуса [6,13]. Фаза опорожнения мочевого пузыря, обеспечиваемая синхронизацией пейсмекеров детрузор (мышечные слои) для формирования перистальтики органа, сопровождается кратковременной релаксацией мышц уретры [8,14].…”
Section: удк 61273+612468unclassified